Perancangan Aplikasi Rekomendasi Shade Complexion Make Up Untuk Menentukan Jenis Foundation Menggunakan Model Rational Unified Process (RUP) Berbasis Web - Widayati, Susi; Chandra, Yudi Irawan (LPPM STIKOM Tunas Bangsa, 2024)
Determining the right foundation shade is a common challenge faced by make-up users, especially for those who have no experience in choosing beauty products. To solve this problem, this research designs a web-based application that can recommend the appropriate foundation shade based on the user's complexion. This application was developed using the Rational Unified Process (RUP) Model, a systematic and structured methodology for software development. The RUP model consists of four main phases: Inception, Elaboration, Construction, and Transition. In the Inception phase, user and stakeholder requirements are identified, as well as initial project planning. The Elaboration phase focuses on system analysis and design, including modeling of functional and non-functional requirements. The Construction phase involves developing and testing the system based on the design that has been created. Finally, the Transition phase focuses on application deployment and user training. This application uses several recommendation algorithms to determine the foundation shade that best suits the user's skin color. User data is obtained through manual input or through photo uploading, which is then analyzed using image processing technology. The results of this analysis are used to identify the user's complexion and provide appropriate foundation shade recommendations. The implementation of the web-based application allows easy and flexible access for users. The application is also equipped with an intuitive and user-friendly interface, making it easier for users to operate and get the desired recommendations. In addition, the app is designed to be continuously updated and adapted to the latest trends in the beauty industry, as well as user feedback. Through the application of the RUP Model, the development of this application is expected to run more efficiently and structured, producing quality products that meet user needs. This app not only helps users in determining the right shade of foundation, but also improves the overall online shopping experience of beauty products.